KRISIS DAN TRANSISI KARIR PADA ORANG DEWASA MENURUT TEORI DONAL SUPER DALAM PERSPEKTIF ISLAM - Mira Eka Marsusi; Muthi’ah Ilfa AF; Masril Masril (STKIP Pesisir Selatan, 2026)
A career crisis is a phenomenon frequently experienced by adults, particularly during the developmental transition phase, characterized by role changes, job uncertainty, and demands for adjustment to the dynamics of life. From a career development perspective, Donald Super explains that individuals go through career stages that allow for crises and transitions as part of the career maturation process. This study aims to analyze the concept of career crisis and transition in adults based on Super's theory and integrate it with an Islamic perspective. The method used is a literature review with a conceptual approach, through the analysis of various scientific literature sources, both from career development theory and Islamic values. The results of the study indicate that career crisis and transition in Super's theory align with the concepts of testing (fitnah), endeavor, and trust in God in Islam, where individuals are encouraged to continue striving, engage in self-reflection, and submit to God in facing career changes. This integration provides a holistic foundation for career counseling that emphasizes not only psychological aspects but also spiritual ones.